Gambaran Sistem Penyimpanan Makanan Kering Di Instalasi Rumah Sakit X Tahun 2022: Overview of Dry Food Storage System in Hospital X Installation in 2022 - Wugha, Astati; Tambunan, Novrida; Hartono, Risky Kusuma (Dohara POAJ, 2025)
Introduction: Storage of food ingredients is an important procedure in hospital nutrition management, involving the systematic organization, storage, maintenance, and documentation of both dry and wet food supplies. The storage and distribution process begins with the receipt of goods at the warehouse, followed by inspection, verification, and recording on warehouse stock cards as part of the inventory control system. After documentation, food ingredients are placed in predetermined storage locations according to hospital standards and nutritional service regulations. Proper food storage greatly contributes to maintaining food quality, ensuring safety, and supporting continuous patient meal service. Methods: This research employed a descriptive qualitative approach. The study was designed to describe storage management practices within the hospital nutrition installation objectively and in detail. The qualitative method allowed in-depth exploration of storage procedures, infrastructure, personnel performance, and compliance with hospital standards. Results: Data were collected through interviews, observations, and document review. Based on the findings, the warehouse personnel were actively involved in the organization and management of food storage. However, there was no special checking procedure for dry food ingredients, and some essential equipment, such as low preparation tables, was unavailable. Operational funds used for storage activities were sourced from the hospital treasurer. Despite certain limitations in equipment and checking procedures, the overall storage process within the Nutrition Installation of Hospital X was carried out in accordance with the applicable Hospital Nutrition Service Standards (PGRS). Conclusion: Storage management at the Nutrition Installation was implemented properly and aligned with PGRS guidelines, although improvements in equipment and inspection procedures are still needed. Keywords: Nutrition Installation, Storage System, Hospital